Fossil beetles as possible evidence for transhumance during the middle and late Holocene in the high mountains of Talysch (Talesh) in NW Iran?. (1st October 2013) - Ponel, Philippe; Andrieu-Ponel, Valérie; Djamali, Morteza; Lahijani, Hamid; Leydet, Michelle; Mashkour, Marjan
Abstract : A short sediment core (300 cm) was retrieved from a peaty deposit in the northeastern corner of Lake Neor in NW Iran yielding a 6500-year-old sequence relatively rich in pollen and beetle remains. Beetle assemblages contained a significant amount of coprophagous and coprophilous species all along the core. Pollen spectra suggest an open steppe landscape typical of the modern Irano-Turanian highlands with pollen indicators of agro-pastoral activities and also the proximity of the mesic temperate Hyrcanian forest to the east. Together, insect and pollen evidence, in agreement with the archaeological evidence for NW Iran, suggest that pastoralism was practised in the high elevation surroundings of Neor in Talysch Mountains at least since ca. 6500 years ago. This preliminary study highlights the strong potential of palaeoentomological investigations in furthering our understanding of the history of pastoralism in the Middle East.